2015
DOI: 10.2147/ahmt.s84806
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of propranolol versus silver nitrate cautery in the treatment of recurrent primary epistaxis in children

Abstract: BackgroundEpistaxis is a common medical problem in pediatric population. Although in most cases it is mild and self-limiting, a proportion of childhood epistaxis is massive, recurrent, or resistant to conventional management.ObjectiveTo compare effectiveness of propranolol as a treatment option for childhood epistaxis versus conventional silver nitrate cautery.Study design and methodologyThis is a prospective interventional comparative study that was carried out during a period of 1 year (January 1, 2013 to De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
13
0
3
Order By: Relevance
“…The authors concluded to the superiority of bipolar electrocautery in children who will not tolerate in-office chemical cautery, in those with a risk of severe bleeding, or when it can be combined with other operative procedures 22. In a recent series of 100 patients with minimal recurrent epistaxis, the recurrence rate was not statistically different between children treated by silver nitrate cauterisation and children treated by propanolol during 1 month 39. Further prospective randomised studies should now be conducted to determine the respective indications of propanolol and electrocautery in children with recurrent idiopathic epistaxis.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded to the superiority of bipolar electrocautery in children who will not tolerate in-office chemical cautery, in those with a risk of severe bleeding, or when it can be combined with other operative procedures 22. In a recent series of 100 patients with minimal recurrent epistaxis, the recurrence rate was not statistically different between children treated by silver nitrate cauterisation and children treated by propanolol during 1 month 39. Further prospective randomised studies should now be conducted to determine the respective indications of propanolol and electrocautery in children with recurrent idiopathic epistaxis.…”
Section: Methodsmentioning
confidence: 99%
“…When the prevention of nosebleeds is discussed, it is important to understand that nose picking, trauma, infection, use of anticoagulation/antiplatelet medications, and hypertension are commonly associated with nosebleeds. 108 Educating caregivers and patients that avoiding digital trauma or nose picking and use of simple nasal hygiene measures are primary strategies to avoid nosebleeds. While most experienced clinicians note that moisturizers and lubricants such as nasal saline, gels, and ointments and use of air humidifiers can help prevent nosebleeds, quality supportive evidence is scarce.…”
Section: Supporting Textmentioning
confidence: 99%
“…It is a common and usually selflimiting clinical condition in childhood (1,2). The incidence of epistaxis is approximately 60 % in all age groups, and emergent inervention was required for 6 % of these patients (3,4).…”
Section: Sayfa 1789mentioning
confidence: 99%